Tindakan Fraud dalam Hal Rekayasa Kredit oleh Pegawai Bank dalam Transaksi Perbankan Dikaitkan dengan Prinsip Kehati- Hatian (Studi Kasus Putusan Nomor 171/PID.SUS-TPK/2022/PN SBY - Nynda Fatmawati Octarina; Fadila Nur Febriyandari (Indo Publishing, 2026)
This study focuses on the application of the banking prudential principle regarding bank employees acting as credit initiators. Credit disbursement procedures rely on the authority of both the credit initiator and the credit approver. The study examines the corruption case registered as Number 171/Pid.Sus-Tpk/2022/PN.Sby. Law Number 10 of 1998 concerning Banking mandates that all bank employees must apply the prudential principle in banking transactions. The case chronology reveals that the defendant engaged in fraudulent activity by orchestrating the disbursement of fictitious customer loans in collusion with other parties for personal gain. The research addresses two issues: first, the application of the prudential principle by the credit initiator in their capacity as the credit processor; and second, an analysis of the involvement of the credit initiator and the credit approver based on the court ruling, alongside an analysis of the fraudulent actions. This study employs statutory, conceptual, and case study research approaches.